Synthesis and cytotoxic activities of some 2-Arylnaphtho [2,3-d]oxazole-4,9-dione derivatives on androgen-dependent (LNCaP) and androgen-independent (PC3) human prostate cancer cell lines - Brandy, Yakini (2011)
The synthesis of five 2-arylnaphtho[2,3-d]oxazole- 4,9-dione derivatives was accomplished by refluxing 2-amino-3-bromo-1,4-naphthoquinone with appropriate benzoyl chloride analogs at elevated temperatures. In vitro anticancer evaluation of these compounds was performed on androgen-dependent, LNCaP, and androgen-independent, PC3, human prostate cancer cell lines. In general, these compounds displayed slightly stronger cytotoxicity on the androgen-dependent LNCaP than on the androgen-independent PC3 prostate cancer cell lines. The meta-substituted 2-(3-Chloro-phenyl)-naphtho[2,3-d]oxazole-4,9- dione (10) appear to display the best cytotoxicity on both cell lines with an IC(50) of 0.03 μM on LNCaP and 0.08 μM on PC3 after 5 days of exposure.